2020
DOI: 10.1111/jocn.15454
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID‐19 outbreak on frontline nurses: A cross‐sectional survey study

Abstract: Aims and objectives: This study aimed to portray the prevalence and associated factors of psychological distress among frontline nurses during COVID-19 outbreak. Background: The COVID-19 outbreak has posed great threat to public health worldwide. Nurses fighting against the epidemic on the frontline might be under great physical and psychological distress. This psychological distress was predominantly described as sleep disturbance, symptoms of anxiety and depression, post-traumatic stress, inability to make d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
268
4
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(360 citation statements)
references
References 41 publications
32
268
4
7
Order By: Relevance
“…And also the prevalence of psychological distress among health-care professionals in this study was higher than the study done in china only on frontline Nurse Professional which shows 25% of nurses had psychological distress according to GHQ they used which might be responsible for the difference in addition to the study population difference. 25 In line with previous research, the majority of participants in this study were highly distressed by COVID-19 related Emotional strain/physical exhaustion, shortages of personal protective equipment, concerns about infecting family members, shortages of ventilators and other crucial medical equipment, fear of limited access to childcare during increased work hours, and Fear of being able to provide competent medical care if deployed to a new area. 17,26,27 Although all health-care workers on duty during the pandemic of COVID-19 are expected to experiencing distress, being married, being nurses and pharmacies, current substance users, working in emergency and outpatient departments, history of chronic medical illness, brief resilient coping level and social support level were particularly associated with high psychological distress.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…And also the prevalence of psychological distress among health-care professionals in this study was higher than the study done in china only on frontline Nurse Professional which shows 25% of nurses had psychological distress according to GHQ they used which might be responsible for the difference in addition to the study population difference. 25 In line with previous research, the majority of participants in this study were highly distressed by COVID-19 related Emotional strain/physical exhaustion, shortages of personal protective equipment, concerns about infecting family members, shortages of ventilators and other crucial medical equipment, fear of limited access to childcare during increased work hours, and Fear of being able to provide competent medical care if deployed to a new area. 17,26,27 Although all health-care workers on duty during the pandemic of COVID-19 are expected to experiencing distress, being married, being nurses and pharmacies, current substance users, working in emergency and outpatient departments, history of chronic medical illness, brief resilient coping level and social support level were particularly associated with high psychological distress.…”
Section: Discussionsupporting
confidence: 83%
“…And also the prevalence of psychological distress among health-care professionals in this study was higher than the study done in china only on frontline Nurse Professional which shows 25% of nurses had psychological distress according to GHQ they used which might be responsible for the difference in addition to the study population difference. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence according to the month of data collected was as follows: February: 32% ( n = 14; 95% CI 25–41; I2 = 98), March: 45% (n = 6; 95% CI 37–53; I2 = 96) and April: 50% ( n = 13; 95% CI 35–66; I2 = 98). Seventeen studies [ 20 , 35 , 36 , 39 , 43 , 44 , 46 , 54 , [57] , [58] , [59] , [60] , [61] , [62] , [63] , 67 , 69 ] involving nurses who were working on the frontline showed stress prevalence at 46% (95% CI = 39–54; I 2 = 97), whereas 20 studies including mixed nurses working in the frontline and second line showed the stress prevalence was 42% (95% CI = 31–53, I 2 = 99). Thirteen studies that used the Perceived Stress Scale (PSS) showed a pooled prevalence of stress at 50% (95% CI = 41–59, I 2 = 98), whereas eight studies [ 35 , 45 , [54] , [55] , [56] , 63 , 64 , 67 ] using the Impact of Event Scale-Revised (IES-R) had a pooled prevalence of 50% (95% CI = 37–63, I 2 = 99).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to understand the factors associated with these behaviors and if they are impaired by the levels of stress these professionals have. A number of studies have assessed the psychological outcomes of the pandemic on health care workers [20][21][22] and the general population [23][24][25][26] but not on dental academics.…”
Section: Introductionmentioning
confidence: 99%